An Analysis of Relationship Between Organization Climate, Work Culture, and Work Environment on Employee Job Satisfaction - Nursakti Nursakti; Ratno Adrianto; Rahmat Bakhtiar; Irfansyah Baharuddin Pakki; Hilda Hilda (GLOBAL HEALTH SCIENCE GROUP, 2025)
The background of this research was based on the importance of job satisfaction in improving the quality of services in the health sector, especially in community health centers. This study aimed to analyze the relationship between organizational climate, work culture, and work environment on job satisfaction of employees at Klandasan Ilir Public Health Center and Manggar Baru Public Health Center in Balikpapan City. The research method used a quantitative approach with a survey technique conducted on employees at both public health centers using a cross-sectional approach. The sampling technique was total sampling with a total of 111 respondents. Data were collected through a questionnaire that included indicators of organizational climate, work culture, work environment, and job satisfaction. Data analysis was conducted using univariate analysis with frequency distribution, bivariate analysis with the chi-square test, and multivariate analysis with logistic regression. The study found that 80.2% of respondents were female, with the majority working in the General Services Unit. Most had a diploma-level education and more than three years of work experience. Bivariate analysis showed significant relationships between job satisfaction and all three independent variables. Multivariate analysis indicated that work culture was the most significant factor influencing job satisfaction (p = 0.001; OR = 0.147). Work culture had the strongest relationship with job satisfaction among Puskesmas employees. Efforts to improve work culture can lead to higher satisfaction and better service quality.